Towards a pedagogical model for teaching through rather than merely with technology: A cultural historical approach - Hardman, J. (South African Journal of Higher Education, 2021)
The global impact of COVID-19, a pandemic that has seen much of the world resort to stringent lockdown rules and the closing of schools, poses challenges for teaching/learning as what was originally a face to face endeavour, has now become an online activity. I have argued in a national newspaper for the distinction between teaching with technology and teaching through technology. In this exploratory article, I engage with this distinction and move towards developing a model of online pedagogy that can lead to learning, in the absence of face to face engagement. The article argues for a pedagogical model capable of delivering content in the absence of a face to face teacher and illustrates this through data from an online intervention with my Honours students. The case study described is exploratory in nature and seeks to understand how an intervention can be set up to effect acquisition, rather than seeking to provide evidence for the success of such an intervention. I draw on the work of Vygotsky (1978) and Hedegaard (1998) to provide a picture of developmental pedagogy that leads to cognitive development. The article argues for how it is possible for online pedagogy to achieve developmental learning by providing findings that indicate how one can teach through technology.